Pipe Dream Play Still - Sam S. Shubert Theater:::Creator::::::::::::
Suzy (Judy Taylor) holding head on lap of Fauna (Helen Traubel)in the musical based off John Steinbeck's 'Sweet Thursday.' The show closed after 245 performances at Sam S. Shubert Theatre in New York. Digital copy only. No hard copy.